In search of the HPA axis activity in unipolar depression patients with childhood trauma: Combined cortisol awakening response and dexamethasone suppression test. (July 2016) - Lu, Shaojia; Gao, Weijia; Huang, Manli; Li, Lingjiang; Xu, Yi
Abstract: The aim of the present study was to examine the impact of childhood trauma on HPA axis activity both in depression patients and healthy controls in order to determine the role of HPA axis abnormalities in depression and to find the differences in HPA axis functioning that may lead certain individuals more susceptible to the depressogenic effects of childhood trauma. Eighty subjects aged 18–45 years were recruited into four study groups (n = 18, depression patients with childhood trauma exposures, CTE/MDD; n = 17, depression patients without childhood adversity, non-CTE/MDD; n = 23, healthy persons with childhood trauma, CTE/non-MDD; and n = 22, healthy persons without childhood adversity, non-CTE/non-MDD). Each participant collected salivary samples in the morning at four time points: immediately upon awakening, 30, 45, and 60 min after awakening for the assessment of CAR and underwent a 1 mg-dexamethasone suppression test (DST). Regardless of depression, subjects with CTE exhibited an enhanced CAR and the CAR areas under the curve to ground (AUCg) were associated with their childhood trauma questionnaire (CTQ) physical neglect scores and CTQ total scores. In addition, the CTE/MDD group also showed a highest post-DST cortisol concentration and a decreased glucocorticoid feedback inhibition among four groups of subjects. The present findings suggested that childhood trauma was associated with hyperactivity of HPA axis as measured with CAR, potentially reflecting the vulnerability for developing depression after early life stress exposures. Moreover, dysfunction of the GR-mediated negative feedback control might contribute to the development of depression after CTE.